GOVERNANÇA CORPORATIVA, RESPONSABILIDADE SOCIAL CORPORATIVA: A VISÃO DE ATORES DE UMA INSTITUIÇÃO DE ENSINO SUPERIOR - IES FEDERAL - Maria da Graça Saraiva Saraiva Nogueira; Tania Elisa Morales Garcia; Maria da Graça Gomes Ramos (Revista Gestão Universitária na América Latina, 2012)
This study aims to identify the main corporate governance (CG), corporate social responsibility (CSR) in an Institution of Higher Education – IHE Federal, through content analysis, interviews with key actors of the organization and his views about this. The methodology used to collect information will be of semi-structured interview, recorded by audio recording and verbatim transcription, with appropriate reading and approval of respondents for the use of its contents in the article presented here. The main results on the CG and the legitimacy, credibility and reliability are present in the institution. Indeed, according to the statements of the respondent we find the integration of management, decision processes that stands for quality and excellence in public education and free. The results relative to CSR found that the IHE study has no formal institutional policies, oriented to the community. Even so, the perception is that the IHE is moving in this direction and believes that institutions do not react proactively in relation to social issues, will be charged by the society itself.